2004
DOI: 10.1002/ejic.200300584
|View full text |Cite
|
Sign up to set email alerts
|

Epoxidation versus Baeyer−Villiger Oxidation: The Possible Role of Lewis Acidity in the Control of Selectivity in Catalysis by Transition Metal Complexes

Abstract: The synthesis of a series of cationic complexes of PtII containing triphos or triphosPO and either a solvent, a hydroxo or a hydroperoxo as the fourth ligand is reported. The complexes are characterized by IR and 31P{1H} NMR spectroscopy and by molar conductivity data, and their Lewis acid characteristics determined by NMR techniques. All complexes are good catalysts for the epoxidation of olefins and the Baeyer−Villiger oxidation of ketones under mild conditions using hydrogen peroxide as oxidant. The latter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The Lewis acid character of metal complexes is a key issue in the activation of oxidants for catalytic oxygen transfer reactions, and in our studies we observed several times that in oxidation processes high activity correlates well with high Lewis acidity of metal catalysts. This applies to both epoxidation 20 and Baeyer−Villiger oxidation of ketones. , Spurred by this general observation we decided to prepare a homologous series of Pt(II) complexes 1a − h (Scheme ), bearing a pentafluorophenyl group and different diphosphine ligands 2a − h , aiming at elucidating the effect of both the activity and selectivity toward alkene epoxidation. Recently, similar complexes bearing alkyl diphosphines were reported in the literature, and now we have extended the procedure to a wide range of diphosphine ligands, following and, in some cases, adapting and improving the previously published procedure (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…The Lewis acid character of metal complexes is a key issue in the activation of oxidants for catalytic oxygen transfer reactions, and in our studies we observed several times that in oxidation processes high activity correlates well with high Lewis acidity of metal catalysts. This applies to both epoxidation 20 and Baeyer−Villiger oxidation of ketones. , Spurred by this general observation we decided to prepare a homologous series of Pt(II) complexes 1a − h (Scheme ), bearing a pentafluorophenyl group and different diphosphine ligands 2a − h , aiming at elucidating the effect of both the activity and selectivity toward alkene epoxidation. Recently, similar complexes bearing alkyl diphosphines were reported in the literature, and now we have extended the procedure to a wide range of diphosphine ligands, following and, in some cases, adapting and improving the previously published procedure (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have also observed that the BV oxidation is very Lewis acid demanding. Thus, the use of highly acidic [(P−P−O)Pt] 2+ type complexes (P−P−O = triphos monoxide) has allowed driving the selectivity toward BV products vs epoxides in the oxidation of unsaturated ketones . This observation prompted us to explore the use of other Lewis acidic Pt(II) complexes with the aim of developing more active and selective catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Lewis-acidic metal centers allows the selective oxidation of unsaturated ketones to the corresponding unsaturated esters without oxidation of the carbon-carbon double bond, indicating that a strong Lewis-acid character of the catalyst can be an important feature in the design of catalysts capable of separating the two processes [115]. Fig.…”
Section: From Alkenesmentioning
confidence: 99%